Perancangan materi, sumber, media, dan bahan ajar dalam pendidikan agama islam (pai) - Muchofifah, Azza Rukyatul (Maliki Interdisciplinary Journal, 2025)
This paper discusses the design of materials, resources, media, and teaching materials in Islamic Religious Education (PAI) as part of efforts to improve learning effectiveness. The design of PAI materials must pay attention to the learning objectives and relevance to the needs of students so that they can understand and internalize Islamic teachings in their daily lives. The learning resources used must be trustworthy and in accordance with the times, including textbooks, digital media, and other references. The use of technology in learning media, such as videos, interactive presentations, and online platforms, can help clarify concepts and increase students’ interest in learning. In addition, the teaching materials developed must be varied, including print and digital methods, in order to provide a more comprehensive learning experience. With a systematic approach in designing materials, resources, media, and teaching materials, PAI learning is expected to be more effective, men.